Novel Insights into Agro-Industrial Waste: Exploring Techno-Economic Viability as an Alternative Source of Water Recovery - Christian I. Cano-Gómez; Cynthia Wong-Arguelles; Jessica Ivonne Hinojosa-López; Diana B. Muñiz-Márquez; Jorge E. Wong-Paz (Waste)
The growing challenges of freshwater scarcity and the high generation of agro-industrial waste, particularly from fruit and vegetable (F&V) processing, pose significant threats to the sustainability of global food systems. F&V waste, which represents a major portion of the 1.3 billion tons of annual food waste, is characterized by a high moisture content (80–95%), making it a largely overlooked but promising source of water recovery. This review critically assesses the techno-economic and environmental feasibility of extracting water from moisture-rich agro-industrial waste streams. Potential technologies such as solar distillation and membrane separation are evaluated to determine their capacity to treat complex organic effluents and recover high-quality water. The potential end uses of reclaimed water in all sectors are explored, focusing on agricultural irrigation, fertigation, industrial reuse and environmental restoration. This study addresses a key research gap and proposes the reclassification of agro-industrial waste as a viable water resource aligned with circular bioeconomy principles and Sustainable Development Goals (SDGs) 6 and 12.